Trajetórias: fissura labiopalatina e imagens - Victorio, Fernanda de Oliveira (2022)
This dissertation contemplates anthropological reflections on the notion of person in the life trajectory of individuals with Complete Bilateral Transforamen Fissure (FTB), a specific type of cleft lip and palate and craniofacial anomaly, of variable presentation, that occurs during the development of the embryo. Attempting to think about the social relationships of patients at the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC/Centrinho), associated with the University of São Paulo (USP), and located in the city of Bauru, this study focuses on the idea that the disease involves a set of latent phenomena that address individual and stigmatizing experiences. The research, which will be carried out from bibliographic studies and my experience as a carrier of the disease, will also rely on the power of images as a way to think about the construction of the notion of person of these individuals and express their human emotions through gestures memorials.